FED Batch Phytoremediation By Salvinia Molesta On Fish Farm Waste Water - Dineshkumar, Muniandy (Universiti Sains Malaysia, 2017)
Phytoremediation is a bioremediation process that uses various types of plants to remove, transfer, stabilize, and destroy contaminants in the soil and groundwater. In this study, the performance of fed batch(FB) phytoremediation by S. molesta, macrophytes on fish farm wastewater is investigated by varying percentage of fresh wastewater loading. This study was aim to investigate the biomass production of S. molesta through different FB percentage cultivation along with nutrient removal aiming to wastewater treatment. The water quality after phytoremediation were monitor throughout study of 16 days. The nutrient removal efficiency was high in higher percentage of FB but all the medium reach standard discharge limit. Ammonia and phosphate removal show very high (˂95%) for 75% FB medium with total removal of 66.55 mg/L and 7.80 mg/L respectively. The removal of ammonia and phosphate by control set was 19.60 mg/L and 2.32 mg/L. Although the concentration of nitrate continues to increase throughout the study, FB cultivation minimized the increment where all percentage experience decrease in nitrate value and 75% FB has lowest level of 2.40 mg/L compare to control where 5.00 mg/L. However total nitrogen value in higher FB medium indicate highest value of 13.85 mg/L on day 16. MLVSS for FB medium is far below control. FB phytoremediation of S. molesta in fish pond water show high efficiency in nutrient removal but negative effect on its biomass, where the final biomass of non-FB is higher than the FB at all percentage. This study proves that FB phytoremediation of S. molesta have potential on nutrient removal from fish farm wastewater.